Obesity Does Not Increase Mortality after Emergency Surgery - Paula Ferrada; Rahul J. Anand; Ajai Malhotra; Michel Aboutanos (Journal of Obesity)
Objective. The aim of this study is to evaluate the impact of obesity on patient outcomes after emergency surgery. Methods. A list of all patients undergoing emergent general surgical procedures during the 12 months ending in July 2012 was obtained from the operating room log. A chart review was performed to obtain the following data: patient characteristics (age, gender, BMI, and preexisting comorbidities), indication for surgery, and outcomes (pulmonary embolus (PE), deep venous thrombosis (DVT), respiratory failure, ICU admission, wound infection, pneumonia, and mortality). Obesity was defined as a BMI over 25. Comparisons of outcomes between obese and nonobese patients were evaluated using Fischer’s exact test. Predictors of mortality were evaluated using logistic regression. Results. 341 patients were identified during the study period. 202 (59%) were obese. Both groups were similar in age (48 for obese versus 47 for nonobese, P=0.42). Obese patients had an increased incidence of diabetes, (27% versus 7%, P<0.05), hypertension (52% versus 34%, P<0.05), and sleep apnea (0% versus 5%, P<0.05). There was a statistically significant increased incidence of postoperative wound infection (obese 9.9% versus nonobese 4.3%, P<0.05) and ICU admission (obese 58% versus nonobese 42%, P=0.01) among the obese patients. Obesity alone was not shown to be a significant risk factor for mortality. Conclusions. A higher BMI is not an independent predictor of mortality after emergency surgery. Obese patients are at a higher risk of developing wound infections and requiring ICU admission after emergent general surgical procedure.